Letramento acadêmico em contexto digital : percepção e experiência de professores em formação no ensino remoto - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
This dissertation deals with academic literacy in digital contexts as a reflection of the need to understand and create strategies in a remote context to improve the new study techniques that this scenario demanded. Therefore, this study aimed to analyze the perception and experience of students in the 4th period of the Letters course about the emergence of academic literacy in emergency remote teaching, in view of language in a digital context, in addition to describe academic literacy practices in the digital context, to recognize the mediations of the learning process regarding the production of academic texts and also to understand the students' perception from the academic literacy practices also occurring in this context. The problem that guided this work was: In what sense can the practice of academic literacy in digital contexts reflect on the production of academic texts? Reflecting on this issue, I realized the relevance of this knowledge in the training of undergraduate students in Letters, since they play two important roles in graduation: students and language teachers in training, because, from this pandemic context, the artifacts of culture will be increasingly present both in academic practices and in the future teaching activities of these students. The research developed here has an interpretive qualitative approach, based on Netnography, as it was possible to access the cultural universe of the participants who interact from the internet through digital culture tools. For the construction of the data, I considered the following instruments: (i) direct observation, in digital form, (ii) a questionnaire with closed and multiple choice questions and discursive questions related to the academic writing practices of the participants; (iii) participants' posts in the virtual classroom. Data analysis was performed based on content analysis by Bardin (1977) and Freitas (in press). The study was carried out through remote activities motivated by social distancing due to Covid-19, supported by the Google platform – Classroom, Meet, Forms. As a theoretical basis, studies by Soares (2009), Kleiman (2008), Marcuschi (2001), Street (2014), Coscarelli (2005), Rojo (2013), Freitas (2021), and others were listed. In this pandemic context, digital genres served as support for teaching activities and with the use of digital language, new genres were required, showing that there are other modalities of text legitimized by academics. However, I realize that it is a little early to affirm, deny or suggest changes in university education, but I believe it would be interesting to rethink the necessary academic literacies from this new context.
Academic literacy in a digital context: perception and experience of teachers in training in remote teaching
Keywords: Cultura digital; Letramento acadêmico; Letramento digital; Multiletramentos; Atividades remotas; Digital Culture; Academic literacy; Digital literacy; Multiliteracies; Remote activities; LINGUISTICA, LETRAS E ARTES::LETRAS